Increased climate seasonality during the late glacial in the Gebel Akhdar, Libya. (15th July 2018) - Reade, Hazel; O'Connell, Tamsin C.; Barker, Graeme; Stevens, Rhiannon E.
Abstract: Oxygen isotope analysis (δ 18 O) of caprine and bovine tooth enamel carbonates from the Haua Fteah cave (Gebel Akhdar massif, northeast Libya) reveals significant differences in palaeoseasonality during the last c. 70 ka. Data indicate different phases of human occupation of the region occurred under notably different climatic conditions. During the last glacial period, prior to the Last Glacial Maximum, a gradual increase in climate aridity occurred. This was followed in the late glacial (c. 16.6–14.7 ka) by considerably more arid conditions and much greater climate seasonality, which was likely produced by changing winter precipitation amounts and a strengthening of arid summer air masses. The high seasonality in the late glacial coincides with a period when human activity at the Haua Fteah greatly intensified. Significant changes in subsistence strategies and the seasonal exploitation of food resources also occurred at this time. The results presented here suggest that changes in the seasonal climate may have affected the seasonal supply of floral and faunal resources available to local human populations at the time, which resulted in changing subsistence practices. Highlights: Climate seasonality in northeast Libya varied over the last 70000 years. The late glacial was characterised by much greater seasonality. Increased seasonality coincided with intensified human activity at the Haua Fteah. Significant changes in the seasonal exploitation of food resources also occurred. Seasonal climate likely affected the seasonal supply of floral and faunal resources.